Respuesta :
Answer:
f(- 1) = 6
Step-by-step explanation:
To evaluate f(- 1) substitute x = - 1 into f(x)
f(- 1) = 3(- 1)² - 2(- 1) + 1 = 3(1) + 2 + 1 = 3 + 2 + 1 = 6
ANSWER:
For the function [tex]f(x)=3 x^{2}-2 x+1[/tex] the value of f(-1) is 6
SOLUTION:
Given, given equation is f(x) = [tex]3 x^{2}-2 x+1[/tex]
Above given equation is quadratic equation.
We need to find the value of f(-1)
For that we have to substitute the value of -1 in place of x in the given quadratic equation.
Now,
[tex]\begin{array}{l}{x=-1 \rightarrow f(-1)=3(-1)^{2}-2(-1)+1} \\ {f(-1)=3(1)-2(-1)+1} \\ {=3(1)-(-2)+1} \\ {=3+2+1} \\ {f(-1)=6}\end{array}[/tex]
Hence, the value of f(-1) is 6.